IMPROVING COLLABORATIVE TECHIQUES IN SCIENCE LEARNING AS A PROSES FOR EARLY CHILHOOD AT KINDERGARTEN CERIA 2 SUMBERMANJING-MALANG - Afifatu Rohmawati (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2025)
The implementation of children's collaborative abilities is a challenge for teachers and parents in creating science learning as a process. Where, students will create science-based works carried out in stages. Science as a process has a complex level of difficulty with a gradual level of difficulty. The purpose of describing collaborative abilities and science learning. The researcher's methodology uses classroom action (CAR), the researcher has a strategy in providing actions to overcome every problem-solving in the class. So that it can be done communicatively in the form of active collaboration. with observation, interview, and documentation data collection techniques. The results of research and learning are carried out based on learning strategy planning, determining learning techniques, and improvement results. The learning strategy emphasizes theme selection and creating creative learning strategies, while the learning techniques use object analysis, experiments, and loose parts. The collaborative concept is carried out in the form of internal teamwork, individual collaboration, and collaboration with external teams/parents. The results of the improvement show that the data for meeting cycle 1 reaches 37.5% - 70%. Meeting cycle 2 reaches 51% - 75%, meeting cycle 3 reaches 65% - 82%. The average cycle results for each meeting reached 54.5% for meeting 1, 63% for meeting 2, and 73% for meeting 3. Therefore, the data shows a significant increase in collaborative skills in science learning from cycle 1 to cycle 2 at each meeting. This represents the latest innovation in learning, in terms of learning strategies, learning techniques, and learning media in every lesson for early childhood.